Pharmacological Effects of RAAS Blockade in Ischemic Nephropathy - Rivoli, Laura; Di Mario, Francesca; Coppolino, Giuseppe; Gigante, Antonietta; Barbano, Biagio; E. Farrah, Tariq; Rosato, Edoardo; Fuiano, Giorgio; Cianci, Rosario (Current Drug Metabolism, 2016)
Background: The management of ischemic nephropathy due to atherosclerotic renal artery stenosis has become increasingly conservative in the modern era, with current guidelines recommending optimized medical therapy as the initial step. The doubts raised by the recently published trials of revascularization strategies have led to a renewed focus on pharmacological strategies promoting blood pressure control and renal protection. It is essential to further elucidate the pathophysiological mechanisms underlying hypoperfusion induced renal microvascular dysfunction with subsequent tissue injury and fibrogenesis. The role of renin angiotensin aldosterone system as a mediator of the main pathophysiological consequences of ischemic nephropathy is well known. However, more recent experimental evidence on the adrenergic system and intrarenal tubular feedback mechanisms has stimulated new interest towards a multi-target therapeutic approach. Methods: This review focuses on the pharmacology of the principle therapeutic drug classes currently used in the treatment of atherosclerotic renal artery stenosis with an analysis of their metabolic aspects and use in clinical practice based on evidence from clinical trials. Results and Conclusions: An optimal pharmacologic approach is crucial for a successful prevention of renal injury and cardiovascular events in this high-risk population. Antihypertensive treatment should include renin angiotensin aldosterone system blockade medication not only for their antihypertensive properties, but especially for those cardio and renoprotective.
Keywords: ischemic nephropathy